2011
DOI: 10.2478/v10011-011-0009-3
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Central Angiotensin Converting Enzyme Exerts Anxiolytic Effects by Decreasing Brain Oxidative Stress

Abstract: Kratak sadr`aj: Ispitivan je uticaj intracere bro ventrikularne administracije angiotenzina II i kaptoprila na napetost i oksidativni stres u mozgu. Za procenjivanje po na{anja bliskog anksioznosti kori{}en je test uzdignutog lavirinta u obliku znaka plus, dok je biohemijska analiza obu hvatila odre|ivanje nekih enzima antioksidantne odbrane kao {to su superoksid-dismutaza i glutation-peroksidaza i pro izvoda lipidne peroksidacije (malondialdehid). Na{i re zultati predstavljaju jo{ jedan dokaz da angiotenzin I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 22 publications
0
23
0
Order By: Relevance
“…It is approximately eight times more active as an inhibitor of ACE activity as compared to trandolaprilat. It also possesses a long elimination half-life, strong lipophilicity, high ACE inhibitor potency, high affinity for the ACE and a long biological half-life (Ciobica et al, 2011).…”
mentioning
confidence: 99%
“…It is approximately eight times more active as an inhibitor of ACE activity as compared to trandolaprilat. It also possesses a long elimination half-life, strong lipophilicity, high ACE inhibitor potency, high affinity for the ACE and a long biological half-life (Ciobica et al, 2011).…”
mentioning
confidence: 99%
“…Oxidative stress is the condition arising from the imbalance between toxic reactive oxygen species (ROS) and antioxidant systems (5), being also recognized as a very important mechanism in a variety of pathologies (6) including neuropsychiatric disorders, as our group has previously demonstrated (7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have led to the identification of two pharmacologically specific angiotensin receptors type 1 (AT 1) and type 2 (AT 2), which are well represented in various brain areas (10). Our group also previously demonstrated that the administration of losartan and PD-123177, which are selective antagonists for the AT 1 and AT 2, re sults in anxiolytic effects in rats (7). Also, similar effects were reported as the result of angiotensin-converting enzyme (ACE) inhibitors like captopril (7), which is also commonly used as an antihypertensive drug (11).…”
Section: Introductionmentioning
confidence: 58%